Do psychological interventions reduce depression in hemodialysis patients?: A meta-analysis of randomized controlled trials following PRISMA. Issue 34 (August 2016) - Xing, Lu; Chen, Ruiqi; Diao, Yongshu; Qian, Jiahui; You, Chao; Jiang, Xiaolian
Abstract: Background: Depression is highly prevalent in hemodialysis patients and results in poor patient outcomes. Although psychological interventions are being developed and used for these patients, there is uncertainty regarding the effectiveness of these interventions. The purpose of this meta-analysis is to evaluate the effects of psychological interventions on depression treatment in hemodialysis patients. Methods: All randomized controlled trials (RCTs) relevant to the depression treatment of hemodialysis patients through psychological interventions were retrieved from the following databases: Embase, Pubmed, PsycINFO, the Cochrane Database of Systematic Reviews, and the Cochrane Central Register of Controlled Trials. The reference lists of identified RCTs were also screened. The Cochrane risk of bias tool was used to evaluate the quality of the studies, RevMan (5.3) was used to analyze the data, and the evidence quality of the combined results was evaluated using GRADE (3.6.1). Results: Eight RCTs were included. The combined results showed that psychological interventions significantly reduced the scores of the Beck Depression Inventory ( P <0.001) and interdialysis weight gain ( P <0.001). However, due to the high heterogeneity, effect size combinations of sleep quality and quality of life were not performed. Conclusion: Psychological interventions may reduce the degree of depression and improve fluid intake restriction adherence. More rigorously designed research is needed.